Degraded pasture distribution and woody enrichment strategies for pasture fertility preservation in the Bragantina region, north-eastern Amazon - Hohnwald, Stefan; Acioli De Abréu, Eliana M.; Krummel, Timo; Trautwein, Julia; Bastos Da Veiga, Jonas; Wollny, Clemens B. A.; Braga, Célia M.; De Azevedo, Calandrini; Gerold, Gerhard (ERDKUNDE, 2010)
In the densely settled Bragantina region, northern Brazil, smallholder cattle pastures start into compulsory degradation processes indicated, among other factors by the woody encroachment of the resprouting secondary vegetation, nationally called capoeira. By means of Landsat and QuickBird satellite imagery techniques different stages of tree-dominated pastures were identified and the distribution of degraded pastures quantified. This was tested in a supervised Landsat classification from 2006 and 2007, taking QuickBird imageries from 2004 and 2005 as additional ground checks. We found that 42% of the rural Bragantinian landscape has already converted into pastures, 28% in advanced stages of above ground pasture degradation. Our reclassification means that the region is still confronted with a serious ecological pasture problem and that conventional land use classifications, climatological models and carbon calculations, based on Landsat imageries only, underestimate pasture distribution and thus lead to inaccurate extrapolations. As the resprouting shrubs of the capoeira are a permanent problem on tropical lowland pastures but, on the other hand, are also the ecological basis of the sustainable slash-and-burn systems of smallholders, we tested some innovative strategies to tolerate various useful woody components of the capoeira on pastures to stabilise them ecologically: first, a buffet trial shows that the ten tested capoeira and some other common domesticated tree species obtain a comparable palatability as well-known woody forage legumes. Thus, Cecropia palmata and Tithonia diversifolia, among others, were as palatable for cattle as the well-known multi-purpose legume Cratylia argentea. As a consequence, these freely accessible tree species should not be slashed but fostered on pastures, like supplementary forage plants. Secondly, it is demonstrated that the multi-purpose forage legumes C. argentea and Flemingia macrophylla perform better under smallholder management than under large scaled farming or even intense management due to the associated prolonged restoration times. In sum, we could demonstrate that woody components (capoeira and/or woody legumes) are more appropriate for the humid tropics than pure grass-monocultures. Based on these experiences, we modified the model of a grass-capoeira-legume pasture, incorporating pastures just as an interim stage of the slash-and-burn system. Forage production could be enhanced in that system by selective slashing of the capoeira (palatable species are tolerated) and by incorporating woody forage legumes. As this biome is known to restore its ecosystem fertility rather in its above-ground biomass than in its poor soils, woody components on pastures are recommended for ecologically sustainable production systems. Furthermore, they might be requisite to mitigate the proclaimed climatic change in the Amazon.